PENGARUH MEDIA PEMBELAJARAN, LINGKUNGAN SEKOLAH, DAN SUPERVISI KLINIS TERHADAP MOTIVASI KERJA GURU DI SMP NEGERI SE KECAMATAN PRACIMANTORO WONOGIRI - Sumardi , Sumardi (2011)
Research purposes is to analyze influence of (1) learning tool, school environment, and clinic supervision to teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District. (2) learning tool to teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District. (3) school environment to teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District. (4) clinic supervision to teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District. Research location was in State Junior High Schools in Pracimantoro Wonogiri District. Research population is entire of State Junior High Schools in Pracimantoro Wonogiri District teachers are 152 teachers. Research samples are 105 teachers based on Nomogram table. Sampling process taken by using Propotionate Stratified Random Sampling. Data analysis by using double linear regression (t test and F test) and classic assumption test (normality test, autocorrelation test, heterocedastisity test, and multicollinearity test). Research results are (1) learning tool variable, school environment, and clinic supervision influencing teacher work motivation with significant level 0,000 < 0,05 and effectiveness as 59,6%. It shows that hypothesis of "Learning tool, school environment, and clinic supervision influencing teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District" is valid. (2) learning tool variable influencing teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District, including significant value as 0,000 < 0,005 and effectiveness as 26,6%. It shows hypothesis of "Learning tool influencing teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District" is valid. (3) school environment variable influencing in one way to teacher work motivation, including significant value 0,012 < 0,05 and effectiveness as 11,6%. It shows that hypothesis of "School environment influencing teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District", is valid. (4) Clinic supervision variable influencing in one way to teacher work motivation, including significant value 0,000 < 0,05 and effectiveness 21,4%. It shows that hypothesis of "Clinic supervision influencing teacher work motivation in State Junior High Schools in Pracimantoro Wonogiri District" is valid.